Assessment of sensory profile and instrumental analyzed attributes influenced by different potassium fertilization levels in three tomato cultivars - Bashar Daoud (Julius Kühn-Institut, 2021)
Sensory properties are an essential quality aspect when the consumption of fresh tomato is under consideration. The flavor of tomato is defined as a combination of taste sensations (sweetness, sourness), aroma (volatile compounds), and texture (firmness, mealiness), some of which are proven to be affected by insufficient nutrient supply − especially potassium (K). This study intends to undertake a holistic assessment of the K fertilization effect on the flavor of tomato by connecting the use of sensorial and instrumental methods. An optimal K supply significantly increased the sensory descriptors sweetness, sourness, and aroma as well as the instrumental estimated color, firmness, total soluble solids (TSS), titratable acids (TA), and dry matter (DM) in a cultivar-specific manner. The volatile organic compounds (VOCs) were not significantly affected by K fertilization. The evaluation by the panelists confirmed the results of the instru-mental analyses, by which an increment in the fruit quality with rising K supply could be detected. An optimal K supply of 3.66 g/plant could be suggested to increase tomato flavor in the cocktail cultivars studied: Primavera and Yellow Submarine. Cultivar effects should, therefore, be considered for defining the optimal K fertilizer dose that favors high tomato fruit quality and, hence, better flavor.